Clinical Significance of Plasma Apolipoprotein-AII Isoforms as a Marker of Pancreatic Exocrine Disorder for Patients with Pancreatic Adenocarcinoma Undergoing Chemoradiotherapy, Paying Attention to Pancreatic Morphological Changes. (4th April 2019) - Hayasaki, Aoi; Murata, Yasuhiro; Usui, Masanobu; Hibi, Taemi; Fujii, Takehiro; Iizawa, Yusuke; Kato, Hiroyuki; Tanemura, Akihiro; Azumi, Yoshinori; Kuriyama, Naohisa; Kishiwada, Masashi; Mizuno, Shugo; et al.
Abstract : Background. Circulating apolipoprotein-AII (apoAII-) ATQ/AT is a potential useful biomarker for early stage pancreatic ductal adenocarcinoma (PDAC), but its clinical significance in PDAC patients remains uncertain. The aim of the current study was to assess the usefulness of apoAII-ATQ/AT as a surrogate for the effect of chemoradiotherapy (CRT) and its association with pancreatic exocrine disorder, paying attention to morphological changes of the pancreas. Methods. In the 264 PDAC patients who were enrolled in our CRT protocol, the following parameters were measured at specified time points before and after CRT: serum levels of albumin, total cholesterol, and amylase as indices of pancreatic exocrine function, serum levels of CA19-9, and the pancreatic morphology including tumor size (TS), main pancreatic duct diameter (MPDD), and pancreatic parenchymal volume excluding tumor volume (PPV) by using computed tomography (CT) images. Plasma apoAII-ATQ/AT levels were simultaneously measured with enzyme-linked immunosorbent assay in 4 healthy volunteers and the 44 PDAC patients before and after CRT. Plasma apoAII-ATQ/AT levels after CRT were analyzed according to small/large-MPDD and small/large-PPV groups based on their median values after CRT. Plasma samples after CRT were measured after incubation with human pancreatic juice (PJ) to examine the relevance between apoAII isoforms and circulating pancreatic enzymes. Results. The serum levels of albumin, amylase, CA19-9, TS, MPDD, and PPV after CRT were significantly lower than those before CRT (median, before vs. after: 3.9 g/dl, 74 U/l, 180.2 U/ml, 58.1 mm, 4.0 mm, and 34.8 ml vs. 3.8, 59, 43.5, 55.6, 3.6, and 25.2). ApoAII-ATQ/AT levels (median, μ g/ml) of PDAC patients before CRT were significantly lower than those in healthy volunteers: 32.9 vs. 61.2, and unexpectedly those after CRT significantly decreased: 14.7. The reduction rate of apoAII-ATQ/AT was not correlated with those of CA19-9 and TS, indicating that apoAII-ATQ/AT is not a tumor-specific marker. On the other hand, the patient group with large MPDD and small PV exhibited higher apoAII-ATQ levels than those with small MPDD and large PPV. The incubation of plasma samples after CRT with PJ did not alter apoAII-ATQ/AT and apoAII-AT levels but significantly decreased apoAII-ATQ levels, suggesting that circulating pancreatic enzymes markedly influenced apoAII-ATQ levels. Conclusions. ApoAII-ATQ/AT levels are not useful for evaluation of clinical effect of CRT for PDAC, but apoAII isoforms are very useful to assess pancreatic exocrine disorder because pancreatic atrophy and insufficient secretion of circulating pancreatic enzymes are considered likely to influence apoAII-ATQ levels.